Hubungan Antara Persepsi Keharmonisan Keluarga dan Konformitas Teman Sebaya Dengan Kenakalan Remaja - Ainiyah Hariz, Siti (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract, Research aimÂ to knowÂ correlation of betweenÂ perception toward family harmony and peer group with juvenile delinquency. Subject research is student of first class SMK 45 in Surabaya as much 91 people. The scales used as the data collects instrument are juvenile delinquency scales, Family harmony perception scales, and peer group scales. Use Scale Likert model which consists of 5 alternative options, while the data analysis method used is regresi analysis.The hypothesis result show that there is relationship between family toward harmony and peer group with juvenile delinquency.Keywords: Perception toward family harmony, peer group, juvenile delinquency